Meckel-Gruber syndrome: a rare and lethal foetal anomaly - Jondhale, Parikshit; Marda, Mohit; Bangal, Vidyadhar B.; Bagdi, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Meckel-Gruber syndrome (MGS) is a rare and lethal autosomal recessive disorder characterized by occipital encephalocele, postaxial polydactyly and bilateral dysplastic cystic kidneys. It can be associated with many other congenital malformations. The incidence of Meckel-Gruber syndrome ranges between 1 in 13,000 to 4,00,000 live births. Antenatal ultrasound examination establishes the diagnosis by identifying at least two of the major features. A case is presented that describes a baby with ambiguous genitalia, who presented with the triad of Meckel-Gruber syndrome. The baby died shortly after birth.